Ultra-Stable and Durable Piezoelectric Nanogenerator with All-Weather Service Capability Based on N Doped 4H-SiC Nanohole Arrays - Zhou, Linlin; Zhu, Laipan; Yang, Tao; Hou, Xinmei; Du, Zhengtao; Cao, Sheng; Wang, Hailong; Chou, Kuo‑Chih; Wang, Zhong Lin (Nano-Micro Letters, 2021)
Ultra-stable piezoelectric nanogenerator (PENG) driven by environmental actuation sources with all-weather service capability is highly desirable. Here, the PENG based on N doped 4H-SiC nanohole arrays (NHAs) is proposed to harvest ambient energy under low/high temperature and relative humidity (RH) conditions. Finite element method simulation of N doped 4H-SiC NHAs in compression mode is developed to evaluate the relationship between nanohole diameter and piezoelectric performance. The density of short circuit current of the assembled PENG reaches 313 nA cm−2, which is 1.57 times the output of PENG based on N doped 4H-SiC nanowire arrays. The enhancement can be attributed to the existence of nanohole sidewalls in NHAs. All-weather service capability of the PENG is verified after being treated at -80/80 ℃ and 0%/100% RH for 50 days. The PENG is promising to be widely used in practice worldwide to harvest biomechanical energy and mechanical energy. Highlights: 1 An ultra-stable all-weather service piezoelectric nanogenerator (PENG) with a wide operating temperature range (-80 80 ℃) and a wide operating relative humidity range (0 100%) is proposed. 2 The PENG based on N doped 4H-SiC exhibits long-term service stability up to 50 days. 3 The short circuit current density of PENG based on N doped 4H-SiC is enhanced significantly.